Innate and adaptive dendritic cell responses to immunotherapy. Issue 6 (December 2015) - Unknown
Abstract : Purpose of review: In allergic disease, dendritic cells play a critical role in orchestrating immune responses to innate stimuli and promoting the formation of T helper 2 (TH 2) effector versus T-regulatory cells. Here, we review recent advances in our understanding of how current forms of immunotherapy modulate dendritic cell responses. Recent findings: Sublingual immunotherapy (SLIT) and oral immunotherapy (OIT) for peanut allergy alter the expression of costimulatory molecules on dendritic cells, which leads to reduced expression of TH 2 effector cytokines in an antigen-nonspecific manner. SLIT and OIT also modulate dendritic cell innate immune responses to Toll-like receptor agonists, including enhanced production of interferon α and reduced expression of proinflammatory cytokines that may serve to promote the development of tolerance. Dendritic cells isolated from patients post-OIT promoted hypomethylation of the FOXP3 locus in effector T cells. Reduced methylation of the FOXP3 locus has been associated with more persistent clinical desensitization following OIT. Recent studies have additionally highlighted a role for B cells in inducing tolerogenic dendritic cell populations and T-regulatory cells during immunotherapy. Epicutaneous immunotherapy may also elicit immunosuppressive populations of cutaneous dendritic cells, although in some cases, antigen exposure through the skin can lead to sensitization. Finally, efforts have focused on identifying pharmacologic and/or antigen-independent strategies of altering dendritic cell function to enhance the immunosuppressive effects of immunotherapy. Summary: Dendritic cells are a critical target of immunotherapy. Alterations in both adaptive and innate immunity likely underlie the immunosuppressive effects of this treatment.